Factors Influencing Risk Management Decision of Small and Medium Scale Enterprises in Ghana - Anselm Komla Abotsi; Gershon Yawo Dake; Richard Abankwa Agyepong (Contemporary Economics)
This research seeks to study the factors that enhance or preclude owners of SMEs in Ghana in making risk management decisions. The study was conducted with managers of SMEs in four regions in Ghana. The researchers adopted a quantitative approach and employed STATA 10 and SPSS version 20 in the analysis. Stratified and simple random sampling techniques were used to select the sample units. The probit model was used in the analysis of data. A total of 447 SMEs were sampled for the study, with at least 111 from each of the selected regions. The probit results show that the demographic factors indicate a positive influence on the likelihood that managers will take risk management decisions. All of the business related demographic factors are significant at various levels and positive, except for risk-loving. The economically related factors, such as the estimated amount at risk, the estimated cost of risk management and the estimated total monthly income after tax all have a positive influence on risk management decision making. However, government and tax policies are perceived to negatively influence risk management decisions by managers. We recommend that institutions working closely with SMEs acquire the expertise to train the managers of SMEs on risk management practices.